Moderasi Beragama dalam Tayangan Anak-anak; Analisis Isi Tayangan Nussa dan Rara Episode Toleransi - Alifa Nur Fitri (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2022)
YouTube is an internet media that has a significant increase and is the most accessed by children during the pandemic. A survey conducted by Jakpat showed an increase in YouTube access from 68.5% to 72.3%. One of the YouTube channels that is widely accessed by children is @nussaofficial. This channel is a program for children and has become one of the favorite programs. however, @nussaofficial cannot be separated from negative responses by accusing the issue of being a radical and intolerant show. One of the influential sources in increasing intolerance in the millennial generation is the internet. This @nussaofficial show appeared because of anxiety about the lack of children's shows that have educational value. This study tries to dissect the @nussaofficial broadcast on the Tolerance Episode with a descriptive qualitative approach. The analysis used is Kripendorf content analysis which aims to determine the content of religious moderation in Nusa shows. Data analysis techniques in this study with Miles and Huberman. The indicators used to determine the message of religious moderation are the four main pillars of religious moderation according to the Ministry of Religion, namely national commitment, harmony, anti-violence and local wisdom through tolerance. The results showed that the @nussaofficial broadcast on the Tolerance Episode contained a message of religious moderation by highlighting the pillars of harmony, anti-violence and local wisdom through tolerance.